Nuclear magnetic resonance of protons on DMSO-02-NaX Zeoli te-system - Hunger, M.; DÂ´Alessandro Martínez, A.; Díaz Pérez, L. (Ciencia, 1970)
A DMSO O2 NaX-zeolite Â system was studied by pulsed protons NMR technique determining the T1 and T2 ”“ relaxation times, and FID at 10 MHz and 89.5 MHz in a tempetature range between 125 K and 355 K. An isotropic rotation of the methv1 group was proposed influenced by a coupling of the DMSO (dimethylsulphoxide) molecule with the zeolitic lattice for the microdanamic motion of this system.